Natural Distribution of the Femoral Mechanical Anatomical Angle in a Portuguese Population with Advanced Knee Osteoarthritis and it’s Implication in Total Knee Arthroplasty Surgical Planning - Buruian, Alexei (2024)
Introduction: Total knee arthroplasty is one of the most successful interventions in medicine. Mechanical alignment remains the gold standard in obtaining a proper coronal prosthetic alignment. There is controversy regarding the use of a fixed cutting angle of the distal femur, with a value between 4o‐7° of valgus that is frequently used intraoperatively. The aim of this study was to describe the distribution of the valgus cut angle in the Portuguese population and to assess the safety of using a fixed valgus cut angle. Methods: From 13.3.2021 to 14.12.2021, 100 pangonograms of patients on the waiting list to undergo total knee arthroplasty, with advanced gonarthrosis, refractory to conservative treatment, were analysed retrospectively and consecutively. Results: The preoperative full length weight bearing radiography of one hundred patients submitted total knee replacement were evaluated, with a mean valgus cut angle of 7.0o± 1.3o (range 3.7o‐10.3o). Conclusion: The use of a fixed resection angle results in a percentage of mechanical axis deviation greater than acceptable (± 3o) in 8%‐68% of cases, as such we conclude that, in order to obtain a proper mechanical alignment, pre‐operative full length weight bearing evaluation is required for proper valgus cut angle measurement.